Reinforcement Schedule Thinning Following Functional Communication Training: Review and Recommendations - Hagopian, Louis P (ABA International, 2011)
This paper extends the Tiger, Hanley, and Bruzek (2008) review of functional communication training (FCT) by reviewing the published literature on reinforcement schedule thinning following FCT. As noted by Tiger et al. and others, schedule thinning may be necessary when the newly acquired communication response occurs excessively, to the extent that reinforcing it consistently is not practical in the natural environment. We provide a review of this literature including a discussion of each of the more commonly used schedule arrangements used for this purpose, outcomes obtained, a description of methods for progressing toward the terminal schedule, and a description of supplemental treatment components aimed at maintaining low levels of problem behavior during schedule thinning. Recommendations for schedule thinning are then provided. Finally, conceptual issues related to the reemergence of problem behavior during schedule thinning and areas for future research are discussed.